Wnt is necessary for mesenchymal to epithelial transition in colorectal cancer cells. Issue 3 (22nd June 2017) - Schwab, Renate H.M.; Amin, Nancy; Flanagan, Dustin J.; Johanson, Timothy M.; Phesse, Toby J.; Vincan, Elizabeth
Abstract : Background: Metastasis underlies most colorectal cancer mortality. Cancer cells spread through the body as single cells or small clusters of cells that have an invasive, mesenchymal, nonproliferative phenotype. At the secondary site, they revert to a proliferative "tumor constructing" epithelial phenotype to rebuild a tumor. We previously developed a unique in vitro three‐dimensional model, called LIM1863‐ Mph, which faithfully recapitulates these reversible transitions that underpin colorectal cancer metastasis. Wnt signaling plays a key role in these transitions and is initiated by the coupling of extracellular Wnt to Frizzled (FZD). Using the LIM1863‐ Mph model system we demonstrated that the Wnt receptor FZD7 is necessary for mesenchymal to epithelial transition (MET). Here we investigate the role of Wnt in MET.Results: Wnt secretion is dependent on palmitoylation by Porcupine (PORC). A PORC inhibitor (IWP2) that prevents Wnt secretion, blocked the epithelial transition of mesenchymal LIM1863‐ Mph cells. Wnt gene array analysis identified several Wnts that are upregulated in epithelial compared with mesenchymal LIM1863‐ Mph cells, suggesting these ligands in MET. Wnt2B was the most abundant differentially expressed Wnt gene. Indeed, recombinant Wnt2B could overcome the IWP2‐mediated block in epithelial transition of mesenchymal LIM1863‐ Mph cells.Conclusions: Wnt2B co‐operates with Frizzled7 to mediate MET in colorectal cancer. Developmental Dynamics 247:521–530, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: The LIM1863‐Mph cells are a unique tissue culture model of the transitions between mesenchymal (tumour invasive front) and epithelial (tumour centre) colorectal cancer cells. Here we show that endogenous Wnt secretion is necessary for epithelial transition of mesenchymal LIM1863‐Mph cells and identify a role for Wnt2B in this process.